Streamlined Approach for Infrapubic Placement of an Inflatable Penile Prosthesis - Edward Karpman (Advances in Urology)
The streamlined approach for infrapubic placement of an inflatable penile prosthesis is a variation of the traditional infrapubic approach. A better understanding of operative techniques and recent clinical outcome studies have led to an evolution of the original infrapubic approach. Small incisions and efficient operative maneuvers can shorten operative times and expedite postoperative recovery.